Analisis Efektivitas Strategi Pemasaran dalam Meningkatkan Ketertarikan Konsumen di Cerita Rasa Nusantara Resto, Jakarta - Deffani, Sheren; Soeprapto, Vishnuvardhana S. (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2024)
In this digital age, marketing is the key to the success of a company, the role of marketing itself is increasingly crucial when the competition is getting tighter plus market conditions tend to change. This intense competition will make consumers face many choices in determining the products they want to buy and consume. Consumers have turned into what is referred to as leisumers (leisure consumers). Experience-based consumption such as vacations, dine-outs, hanging out in cafes, watching concerts, gyms, yoga, to online games is increasing rapidly making the leisure sector grow so fast that it surpasses other sectors, including the restaurant sector which is now improving the quality of its services to meet consumers who have changed their behavior. The purpose of this research is to find out how the effectiveness of the restaurant strategy of cerita rasa nusantara restaurant in marketing its products with the culinary concept of the archipelago when the rise of restaurants rebranding with modern concepts today. This study uses a descriptive quantitative method using a Likert scale on the research instrument. The research population was all customers of the Nusantara flavor story restaurant with a total sample of 96. The results showed that marketing strategy had a significant and positive effect on consumer attraction. This shows that the marketing efforts made by the restaurant have a positive impact on attracting consumer interest, which can lead to an increase in visits and sales of the restaurant.